Pengaruh Beban Kerja dan Stres Kerja Terhadap Turnover Intention Karyawan di The Sanchaya Bintan - Hazmi, Prastu; Wulansari, Nidia; Lisna, Yuke Permata (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This study begins with employee complaints about the heavy workload and work stress caused by work so that it affects Turnover Intention at The Sanchaya Bintan. The purpose of the study was to determine the effect of workload and work stress on Turnover Intention at The Sanchaya Bintan. This type of research is causal associative with a quantitative approach used the survey method, to find out the effect of workload (X1) and work stress (X2) on Turnover Intention (Y) at The Sanchaya Bintan. The population in this study were all employees at The Sanchaya Bintan, with a sample of 115 respondents. The sampling technique used in this study was non-probability sampling with saturated sampling. The data collection technique was carried out by distributing questionnaires using a Likert scale that has been tested for validity and reliability. In testing the hypothesis using the Multiple Linear Regression test, the results of the study are: Data collection techniques are carried out using a questionnaire (questionnaire), whose validity and reliability are tested with a Likert scale. The results of this study are: (1) Workload in the good category (70.5%), (2) Work stress in the good category (71.98%), (3) Turnover Intention in the good category (71.91%). Multiple Linear Regression Test with a calculated F value of 25,538 with a significance of 0.000 <0.05, where the workload and work stress variables have a significant effect on Turnover Intention, with an Adjusted R Square value of 0.301.